Postoperative cervical length to predict success of repeat cerclage in singleton pregnancies with prolapsed membranes after prior cerclage - Park, Suyeon; Lee, Keun-Young; Song, Ji-Eun (Frontiers in Medicine, 2023)
Background: To evaluate the outcome of repeat cerclage (RC) in singleton pregnancies with prolapsed membranes following a prior cerclage and analyze predictive factors for delivery at ≥ 26 weeks of gestation following RC.Patients who underwent RC between 2010 and 2020 at the Hallym University Medical Center were reviewed. Women with singleton pregnancies with prolapsed membranes following prior cerclage were candidates for RC. We analyzed the characteristics, pregnancy outcomes, perioperative clinical and laboratory findings, and postoperative cervical length (CL) to identify the factors for predicting delivery at ≥ 26 weeks following RC.Results: Thirty-five women with RC were identified; the median gestational age (GA) at a prior cerclage was 14 weeks, the average GA at RC was 21+3 weeks, and the median GA at delivery following RC was 26+2 weeks. Patients were divided into two groups based on their delivery status at 26 weeks: 17 women delivered at < 26 weeks (range, 18+4-25+6 weeks) (Group A) and 18 women delivered at ≥ 26 weeks (range, 26+2-40+3 weeks) (Group B). The median GA at delivery in group A was 22+4 weeks, whereas that in group B was 33+4 weeks (p<0.001). No differences in preoperative clinical and laboratory findings were observed between the two groups. However, the postoperative CL in group A was significantly shorter than that in group B (12 mm vs 21.5 mm, p <0.001). The ROC curve of postoperative CL predicting delivery at ≥ 26 weeks showed an AUC of 0.843; a CL of 20 mm showed a sensitivity of 61.1% and a specificity of 100%.RC may prolong singleton pregnancies with prolapsed membranes following prior cerclage. A postoperative CL ≥ 20 mm might predict the success of RC.